2007
DOI: 10.1159/000102931
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Cerebellar Tumour on Language Function in Childhood

Abstract: Background/Aims:Childhood-acquired cerebellar studies to date have appeared to present a concordant pattern of specific neuropsychological profiles depending on lesion site. The aim was to determine the impact of a cerebellar tumour specifically on language function in children by reporting both the general and high-level language abilities of 4 cases with differing sites of hemispheric and vermal involvement. Methods: The language abilities of 4 children (aged from 7 years 9 months to 13 years), treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Early intervention is required with a long-term plan for the management and surveillance of speech and language, as children remain at risk throughout development [15,64,65]. As a group, children receiving surgery and other treatments for brain tumors often experience poor long-term quality of life outcomes due to disorders of speech and language, which include academic failure and loss of friendships that lead to devastating negative impacts upon healthy development and socialization [2,19,33,43,51]. In addition to the effects on existing speech and language functions, skills that are yet to develop are also considered vulnerable, with children failing to acquire or develop skills at the expected rate over time over development [65].…”
Section: Rehabilitation Of Speech and Language Problems During And Afmentioning
confidence: 99%
“…Early intervention is required with a long-term plan for the management and surveillance of speech and language, as children remain at risk throughout development [15,64,65]. As a group, children receiving surgery and other treatments for brain tumors often experience poor long-term quality of life outcomes due to disorders of speech and language, which include academic failure and loss of friendships that lead to devastating negative impacts upon healthy development and socialization [2,19,33,43,51]. In addition to the effects on existing speech and language functions, skills that are yet to develop are also considered vulnerable, with children failing to acquire or develop skills at the expected rate over time over development [65].…”
Section: Rehabilitation Of Speech and Language Problems During And Afmentioning
confidence: 99%
“…Nonetheless, some studies have shown that radiotherapy and tumours in the right cerebellar hemisphere are associated with language disorders. Deficits in high-level language skills, such as the ability to interpret a respond to a conversation, have been identified in children with tumour in the right cerebellum 17 . In this vein, a focus on the narrative skills of children with brain cancer has been recommended 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Children with cancer and nonmalignant hematological disorders (NMHDs) may present with swallowing/feeding dysfunction (eg, dysphagia affecting the oral and pharyngeal phase of the swallow, sensory impairment, behavioral feeding issues) and communication disorders (eg, receptive and expressive language, speech, pragmatics/social language, voice, resonance, stuttering, literacy) that require speech pathology (SP) support (Cornwell, Murdoch, Ward, & Kellie, 2003; Goncalves, Radzinsky, da Silva, Chiari, & Consonni, 2008; Kirk, Howard, & Scott, 1995; Kuruvilla, Perry, Wilson, & El-Hakim, 2009). These disorders may be premorbid, related to lengthy hospitalization, or associated with the child’s cancer or hematological diagnosis (Abramson, Berdon, Ruzal-Shapiro, Stolar, & Garvin, 1993; Ferlito, Rinaldo, & Marioni, 1999; Freeman & Farmer, 1998; Habermann, Kiesler, Dornbusch, & Friedrich, 2000; Ozyar, Cengiz, Gurkaynak, & Atahan, 2005), or treatments and treatment side effects (Buttsworth, Murdoch, & Ozanne, 1993; Docking, Murdoch, & Suppiah, 2007; Epstein et al, 2002; Morgan, Sell, Ryan, Raynsford, & Hayward, 2008; Otmani, 2007; Pollack, Polinko, Albright, Towbin, & Fitz, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These children commonly present with transient mutism following tumor resection, with reported rates of 8% to 25% (Siffert et al, 2000), and 50% to 100% of patients will develop dysarthria (an acquired motor speech disorder) after surgery (Cornwell, Murdoch, Ward, & Kellie, 2003; Kingma, Mooij, Metzemaekers, & Leeuw, 1994; Kirk et al, 1995; Pollack et al, 1995). In addition, these children may have receptive language deficits and high-level language impairments (eg, problem solving, inferencing, use of context; Cornwell, Murdoch, Ward, & Morgan, 2003; Docking et al, 2007; Siffert et al, 2000).…”
Section: Introductionmentioning
confidence: 99%